Triglyceride-glucose index as a predictor of obstructive sleep apnoea severity in the absence of traditional risk factors - Sinem Nedime Sökücü; Şenay Aydın; Celal Satıcı; Seda Tural Önür; Cengiz Özdemir (Arquivos de Neuro-Psiquiatria, 2023)
Objective We evaluated the association between the triglyceride–glucose (TG) index, a marker of insulin resistance, and obstructive sleep apnoea (OSA) severity in patients without diabetes mellitus, obesity, and metabolic syndrome.